Från Gotland till Estland : kyrkokonst och politik under 1200-talet - Markus, Kersti (Mercur Consulting, 1999)
Zusammenfassung.
Keywords: 1200-luku; dominikaanit; keskiaika; kirkkohistoria; kirkkorakennukset; kirkkotaide; sistersiläiset; sisustus; Gotlanti; Ruotsi; Viro